A simplified Parisi ansatz. (15th March 2021) - Franchini, Simone
Abstract: Based on simple combinatorial arguments, we formulate a generalized cavity method where the Random Overlap Structure (ROSt) probability space of Aizenmann, Sims and Starr is obtained in a constructive way, and we use it to give a simplified derivation of the Parisi formula for the free energy of the Sherrington–Kirkpatrick model.